Production and Characterization of the Slime Polysaccharide of Pseudomonas aeruginosa - Evans, Leigh R. (1973)
The slime polysaccharides produced by Pseudomonas aeruginosa isolated from a variety of human infections were investigated. Slime production in culture seemed optimal when adequate amounts of carbohydrate were present and under conditions of either high osmotic pressure or inadequate protein supply. The polysaccharides produced by the organisms were similar to each other, to the slime of Azotobacter vinelandii, and to seaweed alginic acids. They were composed of β-1,4-linked d-mannuronic acid residues and variable amounts of its 5-epimer l-guluronic acid. All bacterial polymers contained o-acetyl groups which are absent in the alginates. The polysaccharides differed considerably in the ratio of mannuronic to guluronic acid content and in the number of o-acetyl groups. The particular composition of the slime was not found to be characteristic for the disease process from which the mucoid variants of P. aeruginosa were obtained.